Engagement With Personalized Feedback for Emotional Distress Among College Students at Elevated Suicide Risk. Issue 2 (March 2022) - Horwitz, Adam G.; Hong, Victor; Eisenberg, Daniel; Zheng, Kai; Albucher, Ronald; Coryell, William; Pistorello, Jacqueline; Favorite, Todd; King, Cheryl A.
Highlights: Elevated-risk students provided option to review personalized feedback (PF) report. A majority (72%) of elevated-risk students chose to review PF at least once. Depression severity and stigma/privacy concerns associated with multiple PF views. Sexual minority students more likely than heterosexual students to review PF. Students not viewing PF were less likely to report low perceived need for services. Abstract: Depression and suicidal ideation have substantially increased among college students, yet many students with clinically significant symptoms do not perceive their distress as warranting mental health services. Personalized feedback (PF) interventions deliver objective data, often electronically, comparing an individual's reported symptoms or behaviors to a group norm. Several studies have shown promise for PF interventions in the context of mood and depression, yet little is known regarding how, and for whom, mood-focused PF interventions might be best deployed. The primary aim of this study was to examine the sociodemographic, clinical, and treatment-seeking factors associated with reviewing PF reports on emotional distress among college students ( N  = 1, 673) screening positive for elevated suicide risk and not receiving mental health treatment. Results indicated that PF engagement was greatest among those with higher depression scores, and those reporting privacy/stigma concerns as barriers to treatment. Sexual minority students were more likely to review their PF than heterosexual students. Taken together, PF interventions may be a useful tool for engaging those with greater clinical acuity, and those hesitant to seek in-person care. Further research is warranted to examine the circumstances in which PF interventions might be used in isolation, or as part of a multitiered intervention strategy.